A correlated shortening of the North and South American monsoon seasons in the past few decades - Arias, Paola A. (2015)
Our observational analysis shows that the wetseasons of the American monsoon systems have shortenedsince 1978 due to correlated earlier retreats of the NorthAmerican monsoon (NAM) and late onsets of the southernAmazon wet season, an important part of the South Americanmonsoon (SAM). These changes are related to thecombination of the global sea surface temperature (SST)warming mode, the El Niño-Southern Oscillation (ENSO),the Atlantic Multidecadal Oscillation (AMO), the westwardshift of the North Atlantic subtropical high (NASH),and the enhancement of Pacific South American and PacificNorth American wave train patterns, which induces variationsof the regional circulation at interannual and decadalscales. The joint contributions from these forcing factorsare associated with a stronger and more equatorwardregional Hadley cell, which enhances convergence towardsthe equator, strengthening and possibly delaying the retreatof the tropical part of the NAM. This in turn accelerates the demise of the northern NAM and delays the reversalof the cross-equatorial flow over South America, reducingmoisture transport to the SAM and delaying its onset. Inaddition, the thermodynamic response to warming appearsto cause local drier land conditions over both regions, reinforcingthe observed changes in these monsoons. Althoughprevious studies have identified the isolated influence of theregional Hadley cell, ENSO, AMO, global SST warming,and NASH on the NAM, the correlated changes betweenNAM and SAM through variations of the cross-equatorialflow had not been established before.